Translational research in veterinary science - Uniwersytet Mikołaja Kopernika w Toruniu ([Nicolaus Copernicus University], 2018)
All aspects related to veterinary sciences including epidemiology, diagnostics, ecological factors related to specific animal diseases and their causative agents as well as broadly understood in-depth molecular analysis of microbiological veterinary pathogens including DNA and RNA sequence analysis as well as so-called -omics research.
Keywords: Veterinary medicine : Periodicals